Assessment of Uterine Arteries Hemodynamic Indexes Changes in Women with Unexplained Infertility - R Mohammadzadeh (Babol University of Medical Sciences, 2009)
BACKGROUND AND OBJECTIVE: Infertility involves pregnancy failure without using preventive measures for a year post intercourse. Transvaginal color Doppler ultrasonography (TCDU) is a method used for infertility diagnosis. Unexplained infertility diagnosed when all standard evaluations of infertility become normal. The uterine arteries hemodynamic indexes (UAHI) as a useful mean for pregnancy evaluation will be changed pre and post gestation. The aim of the present study was to determine UAHI changes in unexplained infertility via TCDU.METHODS: This prospective cohort study was done 50 women with unexplained infertility in Al Zahra hospital, Tabriz in September of 2005. The transvaginal color Doppler ultrasonography performed on patients in the 2nd day of menstruation and post intrauterine insemination. Human chorionic gonadotrophin (HCG) (5000-10000 IU) was intramuscularly injected post dominant follicle observation (17-18 mm diameter). Intra uterine insemination was then performed 24-48 h later. Then, hemodynamic indexes including uterine arteries, endometrial thickness and echogenicity were measured by sonography and compared in pregnant and non pregnant groups.FINDINGS: No significant difference found between mean right and left uterine arteries hemodynamic indexes on 2nd day of menstruation and HCG injection day in non-pregnant and pregnant groups. Mean pulsatility index was raised with the increase of endometrial thickness in non-pregnant and decreased with the increase of endometrial thickness in pregnant women.CONCLUSION: The present study showed that uterine arteries hemodynamic index changes may not be a reliable method to evaluate pregnancy in women with unexplained infertility.